Design of tool and backing/clamping system for dissimilar friction stir welding of high strength AA7075-T6 AND AA2024-T351 aluminum alloys - Hasan, Mohammed Midhat (2017)
This work was carried out on dissimilar metal joining of the hard-to-weld aluminum alloys, which has become an important application in the modern industries. The study aims on producing defects-free welds of high strength AA7075-T6 and AA2024-T351 aluminum alloys by the friction stir welding (FSW), which has been proposed as an alternative welding method. The experimental setup was developed through introducing proper design of welding tool and backing/clamping system, considering the process variables (welding speeds, tool tilt angle, clamping force, dwell sequence and relative materials position and orientation). Different pin tool profiles (cylindrical and tapered, smooth and threaded, flatted and non-flatted) were investigated in conjunction with varying levels of machine variables through the central composite design method. To reduce the total cost, the workpieces in this level of the study were prepared from the widely used AA6061 and high strength AA7075 aluminum alloys. Tool design was further studied by considering the influence of pin tool flute radius on the material flow and tensile properties of the dissimilar weld. A new method of two-stage welding without applying the ordinary plunge phase was introduced to avoid the longitudinal pin tool wear. To control the total heat of welding process, three backing and cover systems consisted of high and low thermal conductivity materials were used. In addition, a new construction of asymmetric backing and cover system was introduced to access the temperature distribution during the welding process, which was observed using imbedded thermocouple wires. Visual inspection, metallographic analysis, hardness distribution and tensile properties were conducted to detect the weld quality. The results showed that the joint strength can be enhanced up to 31% when a straight cylindrical pin tool is truncated, threaded and machined with single flat. It was also noticed that the weld quality can be further improved when the additional flat is modified to a single flute with a radius equal to that of the pin tool radius. The dissimilar AA7075-AA2024 weld strength of about 400 MPa, which represents an efficiency of 89% was recorded when the softer AA2024 alloy was fixed on the advancing side at 900 rpm of spindle speed, 100 mm/min of traverse rate, 3° of tilting angle and moderate clamping pressure of 3 kN. The efficiency was increased to 91.6% when the traverse rate was raised to 150 mm/min under the same process variables. Defect-free weld was produced after 12 seconds of stationary delay time. The most stable weld was attained by using the two-stage welding method, which significantly reduced the longitudinal deformation of the pin tool caused from the plunging cycle. The results clarified that the effect of backing and clamping materials on the weld strength is changed related to the applied welding speed. Moreover, a considerable difference in process temperature was noticed between the advancing and retreating sides of the weld. The temperatures were higher on the advancing side compared to those measured on the retreating side. The asymmetric backing/clamping system extracted more amount of the welding heat from the advancing side and reduced the temperature asymmetry. This in turn enhanced the weld strength up to 426 MPa, which represents the maximum joint efficiency of about 95%. In addition to the other FSW process variables, design of the welding tool and backing/clamping system affect the pattern of material flow, temperature distribution, hardness profile and hence weld quality. The outcomes of the present study provided advanced knowledge for the future work in dissimilar metal joining.